UJI UNJUK KERJA ALAT PENGERING TIPE RAK MODEL TETA’17 PADA PENGERINGAN BIJI PALA - Rosnawati M. Kasim; Douwes D. Malik; Handry Rawung (Universitas Sam Ratulangi, 2017)
ABSTRACTNutmeg (Myristica Fragrans Houtt) is a native Indonesian plant that is very potential as a commodity trading at home and abroad. It has long been known as a spice plant and has an important position as a source of essential oil needed in various industries, such as food, medicine, perfume, cosmetics, and others (Rukmana, 2004). Nutmeg plants have the advantage that almost all parts of the fruit can be used, ranging from the fuli (red objects that wrap the skin of the seeds), nutmeg and nutmeg flesh. The aim of this research is to determine the characteristics of drying of nutmeg seed using rack type dryers including temperature change, relative humidity, material weight, airflow rate, air volume flow rate, water content of material, time of drying rate, and drying rate water. This research uses descriptive method of drying process used temperature below 55˚C repeated as much as 3 (three) times until reaching water content 8 - 10% bk. The result of the observation showed that during the drying process there was recorded an outer Rh of the dryer between 83.28% -89.50%. Also the Rh in the dryer was observed and recorded ranging from 86.58% -97.91%. The moisture content of the nutmeg during the drying process decreased from 38.75% down to an average of 18.05% with the details on the shelf one 6.54%, the shelf two 8.28% and the third rack 9.70%. With a 12 hour observation time.Keywords: Model shelf dryers teta'17 models